Gummy smile: A contemporary and multidisciplinary overview - Marcelo Tomás Oliveira; Gustavo Otoboni Molina; Alvaro Furtado; Janaina Salomon Ghizoni; Jefferson Ricardo Pereira (Wolters Kluwer Medknow Publications, 2013)
The aim of this study was to elucidate the diagnosis, etiology, and therapeutic options for the treatment of gummy smile. The smile level is an imaginary line after the lower superior lip and used seems to be convex. The presence of 3 mm or grater continuous gingival band exposures to natural smile or speech performs the gummy smile. Original articles studying the diagnosis, etiology, and therapeutic alternatives for the treatment of gummy smile were searched in the Medline, Scopus, Science direct, and EBSCO host databases. Together with some example and diagnosis method was purposed. The authors conclude that the etiology is multifactorial and can be showed excessive vertical maxillary grow up, excessive labial contraction, shorter upper lip, gingival excess, and extrusion of the anterior teeth. The therapeutics alternative are often multidisciplinary, besides can be used orthognathic, plastic and periodontal surgery, and orthodontic.